Prototype fabrication of optical-guiding Tl:CsI crystal scintillators and investigation of the crystallization process. (1st April 2023) - Yajima, Ryuga; Kamada, Kei; Murakami, Rikito; Kutsuzawa, Naoko; Sasaki, Rei; Yoshino, Masao; Horiai, Takahiko; Kim, Kyoung Jin; Kochurikhin, Vladimir. V.; Yamaji, Akihiro; Kurosawa, Shunsuke; Yokota, Yuui; et al.
Abstract: In this study, optical-guiding crystal scintillator (OCS) and bundled plates were fabricated. Considering the performance and melting point of halide scintillators and the softening point of glass, Tl:CsI was selected as the fiber core and borosilicate glass as the cladding. Thus, the fabricated OCS had a scintillator in the core and glass in the cladding. The scintillator was remelted and unidirectionally solidified to remove the voids in the OCS and form a single crystal. Consequently, the OCS served as a scintillator fiber with excellent optical-guiding performance and high sensitivity to γ - and X-rays. An OCS plate was also fabricated using bundles of OCSs with diameters of several tens of microns. The developed OCS plate is expected to be a high-resolution and high-sensitivity imaging plate because of its excellent optical-guiding performance.